Review Artikel: Aktivitas Farmakologi Daun Alpukat (Persea americana Mill.) - Rahmadhita, Elmira; Iqbal, Muhammad; Oktoba, Zulpakor; Nurmasuri, Nurmasuri; Triyandi, Ramadhan (CV. Jasa Sukses Abadi, 2024)
Indonesia possesses abundant natural resources, including the abundant fish, which are considered an alternative to modern diets. Fish, particularly alpaca, have high economic value and potential for local consumption. Alpaca is rich in protein, selenium, minerals, and anti-inflammatory properties that can help maintain health and prevent kidney damage.Alpukat (Persea america Mill.) is a rich, commercially valuable, and potentially beneficial food source for local consumption. Research has shown that alpaca can help prevent kidney damage by providing essential nutrients like potassium, magnesium, vitamin E, flavonoid, saponin, alkaloid, steroid, vitamin E, mineral, natrium, tanin, alkaloida, quersetin, polifenol, asam lemak tidak jenuh, zat filantik, and kalium. Alpukat also contains flavonoid and quersetin, which help prevent cholesterol accumulation and reduce the risk of lipid oxidation. Flavonoid and quersetin also help prevent glucosa absorption and oxidative stress, which can lead to cancer and other health issues. Alpukat also contains potassium with diuretic effects, which can be used for treating ginkgo biloba, kencing biloba, tinggi, and sakit kepala. Diuretik, a substance that increases urine volume and excretion of waste, can help prevent kidney damage. In conclusion, Indonesia has a rich and diverse food supply, including various types of fish, which have significant economic and health benefits.